Analysis of arrhythmia and its risk factors in patients with COVID-19 - Wenzhao Guan; Meihua Liu; Shuling Rong; Tianpei Liu; Xiaolin Wang (PLoS ONE, 2025)
Background To investigate the incidence of arrhythmia in patients with coronavirus disease 2019 (COVID-19) and analyze its risk factors. Methods This was a retrospective cross-sectional study that surveyed 324 COVID-19 patients admitted to the Second Hospital of Shanxi Medical University from 2020 to 2022. General data, vital signs, myocardial enzyme and imaging data of the patients were collected. The characteristics of COVID-19 patients with arrhythmia were analysed, and multivariate logistic regression was used to analyze the risk factors for arrhythmia in patients. The receiver operating characteristic (ROC) curve was plotted to evaluate the efficacy of the regression equation in predicting arrhythmia in COVID-19 patients. Results Compared with COVID-19 patients without arrhythmia, those with arrhythmia were found to have significant differences in heart rate, prothrombin time (PT), activated partial thromboplastin time (APTT), blood glucose, uric acid, serum potassium, serum total cholesterol, high-sensitivity troponin I (hs-TnI), N-terminal pro B-type natriuretic peptide (NT-proBNP), aortic root diameter, left atrial diameter (LAD), left ventricular end-diastolic diameter (LVEDD), left ventricular ejection fraction (LVEF), fractional shortening (FS), end-systolic volume (ESV), and diabetes (all P < 0.05). Multivariate logistic regression analysis revealed that heart rate, PT, hs-TnI, ESV, serum potassium, blood glucose and diabetes were risk factors for arrhythmia in COVID-19 patients (all P < 0.05). ROC curve analysis showed that the area under the curve (AUC) was 0.773 (95%CI: 0.711-0.834, P < 0.001). Conclusion Heart rate, PT, hs-TnI, ESV, serum potassium, blood glucose and diabetes are risk factors for arrhythmia in COVID-19 patients.